Quantitative Diffusion Tensor Imaging Tractography Metrics are Associated with Cognitive Performance Among HIV-Infected Patients - Tate, David F. (2010)
There have been many studies examining HIV-infection-related alterations of magnetic resonance imaging (MRI) diffusion metrics. However, examining scalar diffusion metrics ignores the orientation aspect of diffusion imaging, which can be captured with tractography. We examined five different tractography metrics obtained from global tractography maps (global tractography FA, average tube length, normalized number of streamtubes, normalized weighted streamtube length, and normalized total number of tubes generated) for differences between HIV positive and negative patients and the association between the metrics and clinical variables of disease severity. We also examined the relationship between these metrics and cognitive performance across a wide range of cognitive domains for the HIV positive and negative patient groups separately. The results demonstrated a significant difference between the groups for global tractography FA (t=2.13, p= 0.04), but not for any of the other tractography metrics examined (p-value range=0.39 to 0.95). There were also several significant associations between the tractography metrics and cognitive performance (i.e., tapping rates, switching 1 and 2, verbal interference, mazes; r≥0.42) for HIV infected patients. In particular, associations were noted between tractography metrics, speed of processing, fine motor control/speed, and executive function for the HIV-infected patients. These findings suggest that tractography metrics capture clinically relevant information regarding cognitive performance among HIV infected patients and suggests the importance of subtle white matter changes in examining cognitive performance.